2018
DOI: 10.1111/jocn.14336
|View full text |Cite
|
Sign up to set email alerts
|

Association between dehydration on admission and postoperative complications in older persons undergoing orthopaedic surgery

Abstract: Given its significant influence on care outcomes and postoperative recovery, hydration care that promotes early recognition and timely management of dehydration is an integral part of fundamental care for older persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 27 publications
(89 reference statements)
2
13
2
Order By: Relevance
“…We found dehydrated patients to have a mean LOS almost twice as long as nondehydrated patients, although our multivariate analysis did not identify any significant association between LOS and dehydration. None of the complications we examined were found to be significantly associated with dehydration, which is in contrast to previous reports in the surgical literature that showed dehydration to be significantly correlated with respiratory, gastrointestinal, and hematologic complications 8 …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found dehydrated patients to have a mean LOS almost twice as long as nondehydrated patients, although our multivariate analysis did not identify any significant association between LOS and dehydration. None of the complications we examined were found to be significantly associated with dehydration, which is in contrast to previous reports in the surgical literature that showed dehydration to be significantly correlated with respiratory, gastrointestinal, and hematologic complications 8 …”
Section: Discussioncontrasting
confidence: 99%
“…However, on multivariate regression analysis, age between 61 and 80 years was found to be significantly associated with dehydration, although this finding had low precision with a wide CI. Currently, there is discrepancy in the surgical literature as to which comorbidities are associated with preoperative dehydration in surgical patients 8,9 . This study showed dependent functional status to be a significant determinant of hydration status only on univariate analysis, and not in the multivariate model, suggesting the presence of confounding factors associated with both dehydration and functional status.…”
Section: Discussioncontrasting
confidence: 54%
“…These conclusions were not supported by our findings. Chan et al ., after examining the records of 216 patients, concluded that patients who had preoperative dehydration status were more likely to experience hematologic or gastrointestinal postoperative complications which is consistent with our finding of increased need for blood transfusion in both THA and TKA patients who were dehydrated prior to surgery [ 12 ]. The main difference between our study and the studies previously mentioned is that previous studies examined orthopedic surgeries more broadly, rather than patients specifically undergoing elective THA and TKA.…”
Section: Discussionsupporting
confidence: 78%
“…Another widely adopted metric for assessing hydration status is the Blood Urea Nitrogen (BUN)/Creatinine (Cr) ratio. In the literature, thresholds for the dehydrated state range from a ratio greater than 15 to a ratio greater than 25, but the threshold is most commonly set at a ratio greater than 20 [ 12 , 13 ]. However, the relationship between preoperative hydration status and postoperative complications in total joint arthroplasty is largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperosmotic dehydration traditionally refers to a total body water deficit often induced by a combination of restricted fluid intake and exposure to adverse environments . Fluid volume depletion is associated with poorer health outcomes when concomitant with chronic diseases, increased mortality among elderly and intensive care patients, decreased physical and cognitive performance, and impaired postoperative recovery …”
Section: Introductionmentioning
confidence: 99%